VDGA-Based Resistorless Dual-Mode SIMO Biquadratic Filter - Pimpol, Jirapun; Channumsin, Orapin; Pukkalanun, Tattaya; Tangsrirat, Worapong (My University, 2024)
This work introduces the synthesis of a resistorless single-input multiple-output dual-mode biquadratic filter. The proposed circuit can perform both voltage-mode and current-mode operations without making circuit modifications. It consists of two voltage differencing gain amplifiers (VDGAs) as an active element, together with only two grounded capacitors as passive elements. Furthermore, it has the capability to produce the conventional biquad filter functions - namely, simultaneous highpass, bandpass, and lowpass responses - in either voltage or current mode. The proposed dual-mode biquad filter can electronically adjust significant filter parameters. TSMC 0.25-μ m CMOS process parameters are utilized in computer simulation to validate the theoretical expectations.
Keywords: Dual-mode circuit (DM); electronically controllable; single-input multiple-output (SIMO); Voltage Differencing Gain Amplifier (VDGA)